2021
DOI: 10.3390/ijerph182111169
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Changes in Travel Behavior during the COVID-19 Pandemic: The Role of Tourists’ Personalities

Abstract: This study investigates travel behavior and psychosocial factors that influence it during the COVID-19 pandemic. In a cross-sectional study, using an online survey, we examined changes in travel behavior and preferences after lifting travel restrictions, and how these changes were influenced by exposure to COVID-19, COVID-19 travel-related risk and severity, personality, fear of travel, coping, and self-efficacy appraisals in the Romanian population. Our results showed that participants traveled less in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…This is proved by previous research showing that travelers' responses to a pandemic outbreak usually result in concern over their safety and perceptions about disease transmission, which changes their travel patterns [9,10]. Morar et al [11] found that fear of travel and neuropsychological personality factors may influence travel behavior in the pandemic era. Furthermore, Wen et al [12] anticipated that tourists traveling in the post-COVID-19 era will be disinclined to participate in mass tourism, preferring more deliberate trips focused on responsible experiences.…”
Section: Introductionmentioning
confidence: 89%
“…This is proved by previous research showing that travelers' responses to a pandemic outbreak usually result in concern over their safety and perceptions about disease transmission, which changes their travel patterns [9,10]. Morar et al [11] found that fear of travel and neuropsychological personality factors may influence travel behavior in the pandemic era. Furthermore, Wen et al [12] anticipated that tourists traveling in the post-COVID-19 era will be disinclined to participate in mass tourism, preferring more deliberate trips focused on responsible experiences.…”
Section: Introductionmentioning
confidence: 89%
“…Given the need to restore tourism, the possibility that SARS-CoV-2 will be an endemic virus that will last for extended periods in many regions [ 61 ], and the requirements for booster COVID-19 vaccines for travel reasons, research is needed to assess the intention to get the COVID-19 vaccine for travel purposes. Furthermore, to ensure travel restoration under the existence of vaccination, travel promotion campaigns and communication efforts must use research-based strategies on sociodemographic and psychosocial variables [ 13 ]. We also explored the differences in travel behavior between vaccinated and unvaccinated individuals during a relaxation period (several months after lifting the COVID-19 related restrictions) before wave four in Romania.…”
Section: The Studymentioning
confidence: 99%
“…Furthermore, the possibility that SARS-CoV-2 virus will be present in the future in some regions imposes the necessity of vaccination for travel reasons to individuals traveling from or to regions with higher rates of COVID-19 infections. Assessing the predictors of vaccination for travel reasons may help our understanding of vaccination behavior [ 7 , 8 , 9 ] and the involved risks potentially harmful to human health and to the physical built environment [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since COVID-19 has dramatically changed tourists’ psychological attitudes [ 14 ], the travel pattern becomes selective, and some projected tourism trends may drive future tourism, such as independent travel, luxury trips and health and wellness tourism [ 7 ]. Although researchers have suggested some possible tourism patterns [ 15 ], they have not considered the travel restrictions that influence tourists’ motivation and perception to travel [ 16 ]. Although COVID-19 vaccines are probably one of the best ways to help the tourism economy recover, it is not a “free pass”.…”
Section: Theoretical Backgroundmentioning
confidence: 99%